Efektivitas Media Board Game Monopoly Terhadap Hasil Belajar Siswa Sekolah Dasar pada Materi Salat Rawatib - Resfita, Devi; Yulianengsih, Neng Lia (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Low student learning outcomes in the Islamic Religious Education (PAI) subject indicate a need for more innovative and interactive learning media. This study aims to determine the differences and improvements in student learning outcomes before and after using a Monopoly-style board game as a learning medium for the topic